New wines into the androgynous bottle: Angela Carter’s discourse on androgyny in The Passion of New Eve and Orlando, or the Enigma of the Sexes - Stephan, Leandro Batista (2025)
The concept of androgyny has had many meanings through history, from a Platonic idea of androgynous dual bodies derived from sexual division to Foucault’s conceptualization of modern homosexuality. In this dissertation, we argue that Angela Carter proposes a new meaning to this phrase by defining androgyny as a form of relation between individuals that overcomes the inherently oppressive terms of sexualized existences. We analyze Carter’s novel The Passion of New Eve and her libretto Orlando, or the Enigma of the Sexes in order to theorize what we name relational androgyny. In order to do that, we use an archeological method, based on Foucault’s The Archeology of Knowledge, and we develop analyses of Carter’s essay The Sadeian Woman and the Ideology of Pornography. We argue that, by introducing the relational factor into the discussion of androgyny, Angela Carter disrupts the concept of androgyny itself. That is to say, that by adding a new wine to an old bottle, she causes the bottle to explode. Keywords: androgyny; Angela Carter; queer theory; English literature